Anionic sigmatropic-electrocyclic-Chugaev cascades: accessing 12-aryl-5-(methylthiocarbonylthio)tetracenes and a related anthra[2,3-b]thiophene - Burroughs, Laurence; Ritchie, John; Ngwenya, Mkhethwa; Khan, Dilfaraz; Lewis, William; Woodward, Simon (Beilstein-Institut, 2015)
1,4-Diols resulting from the double addition of ArCCLi (Ar = Ph, substituted phenyl, 2-thienyl) to ortho-C6H4(CHO)2 undergo cascades to tetracenes on simple admixture of LiHDMS, CS2 and MeI. Acene formation proceeds by [3,3]-sigmatropic rearrangement of xanthate anions followed by 6π electrocyclisations. The reactions are terminated by E2 or anionic Chugaev-type eliminations. Structural packing motifs and electronic properties are reported for the tetracenes.